2014
DOI: 10.1002/stem.1672
|View full text |Cite
|
Sign up to set email alerts
|

PRL2/PTP4A2 Phosphatase Is Important for Hematopoietic Stem Cell Self-Renewal

Abstract: Hematopoietic stem cell (HSC) self-renewal is tightly controlled by cytokines and other signals in the microenvironment. While stem cell factor (SCF) is an early acting cytokine that activates the receptor tyrosine kinase KIT and promotes HSC maintenance, how SCF/KIT signaling is regulated in hematopoietic stem cells is poorly understood. The protein tyrosine phosphatase 4A (PTP4A) family [aka PRL (phosphatase of regenerating liver) phosphatases], consisting of PTP4A1/PRL1, PTP4A2/PRL2 and PTP4A3/PRL3, represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 50 publications
(110 reference statements)
2
53
1
Order By: Relevance
“…There were no differences in brain, thymus, heart, kidney, and liver weight between PRL2-KO and WT mice ( Figure 2C and Supplemental Figure 2). Spleen weight was reduced in both sexes, as reported previously (20), while the weights of both the white adipose tissue (WAT) and the brown adipose tissue (BAT) were significantly reduced in male PRL2-KOs, but not in female KOs (Figure 2, B and C). In agreement with these findings, histological analyses also revealed the size of adipocyte in WAT (Figure 2, D and E) and the percentage of lipid droplet area in BAT (Figure 2, D and F) were significantly reduced in male PRL2-KO vs. WT males.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…There were no differences in brain, thymus, heart, kidney, and liver weight between PRL2-KO and WT mice ( Figure 2C and Supplemental Figure 2). Spleen weight was reduced in both sexes, as reported previously (20), while the weights of both the white adipose tissue (WAT) and the brown adipose tissue (BAT) were significantly reduced in male PRL2-KOs, but not in female KOs (Figure 2, B and C). In agreement with these findings, histological analyses also revealed the size of adipocyte in WAT (Figure 2, D and E) and the percentage of lipid droplet area in BAT (Figure 2, D and F) were significantly reduced in male PRL2-KO vs. WT males.…”
Section: Resultssupporting
confidence: 85%
“…Among the 3 PRLs, PRL2 is the most ubiquitously expressed in mammals (15,17). Moreover, analysis of PRL2-deficient mice revealed that PRL2 is required for proper placental development (18), spermatogenesis (19), and hematopoietic stem cell self-renewal (20).…”
Section: +mentioning
confidence: 99%
“…Gain-of-function mutations in SHP2 cause a myeloproliferative disorder, and SHP2 is essential for oncogenic c-KIT transformation to myeloproliferative disease (9,10). Recently, the intracytoplasmic phosphatase of regenerating liver PRL2 was found to be important for SCFmediated HSC self renewal (11). In addition to the intracytoplasmic PTPs, there are 21 distinct receptor PTPs.…”
Section: Introductionmentioning
confidence: 99%
“…PRL2 null HSPCs are more quiescent and less proliferative. 32 Both p21 and p57 have been shown to regulate HSPC proliferation 34,35 and we observed decreased expression of p21 and p57 in PRL2 null hematopoietic stem and progenitor cells; 32 therefore, PRL2 plays an important role in promoting HSPC proliferation, at least in part, by controlling the level of cell cycle regulators. How PRL2 regulates the expression of these cell cycle regulators is not clear.…”
Section: Prl2 Regulates Hematopoietic Stem Cell Proliferationmentioning
confidence: 71%
“…1), suggesting that it could play an important role in lineage commitment. 32 To define the role of PRL2 in regulating hematopoietic stem cell self-renewal, we performed serial bone marrow transplantation assays and found that loss of PRL2 impairs the ability of haematopoietic stem cells to repopulate the lethally irradiated recipient mice. The decreased selfrenewal capability is not due to homing defects or increased HSC apoptosis, demonstrating that PRL2 regulates hematopoietic stem cell self-renewal in a cell autonomous manner.…”
Section: Prl2 Regulates Haematopoietic Stem Cell Self-renewalmentioning
confidence: 99%